Jews and the Military : A History - Penslar, Derek Jonathan (Book collections on Project MUSE., 2013)
Jews and the Military is the first comprehensive and comparative look at Jews' involvement in the military and their attitudes toward war from the 1600s until the creation of the state of Israel in 1948. Derek Penslar shows that although Jews have often been described as people who shun the army, in fact they have frequently been willing, even eager, to do military service, and only a minuscule minority have been pacifists. Penslar demonstrates that Israel's military ethos did not emerge from a vacuum and that long before the state's establishment, Jews had a vested interest in military affairs. Spanning Europe, North America, and the Middle East, the book discusses the myths and realities of Jewish draft dodging, how Jews reacted to facing their coreligionists in battle, the careers of Jewish officers and their reception in the Jewish community, the effects of World War I on Jewish veterans, and Jewish participation in the Spanish Civil War and World War II.